Optimization of components design and assembly process using DFMA analysis: A case study of bread toaster - Subramanian, Nanthakumaran; Nawawi, Azli (Progress in Engineering Application and Technology, 2022)
Every sector needs a low-cost, high-quality product with a shorter time to market ability. Design for Manufacturing and Assembly (DFMA) is a manufacturing-related process that can be used to decrease or redesign various items. The advantage of DFMA is that it can optimize the design and assembly time of a product. The main goal of this research is to offer a new bread toaster design. In addition, in order to support the improvements, components design, manufacturing cost, assembly time, and design efficiency are being examined. The study was carried out by disassembling the bread toaster, observing the functioning of each component, 3D modeling with Solid Works software, and finally applying the DFMA design principles to the operation cost, time, and design efficiency. The selection criteria for a successful design are based on the cost of manufacture and the time of assembly. Finally, the design chosen has been proven to meet all the relevant requirements by improving in the operation cost, operation time and design efficiency. The existing product design efficiency is 33 % and the new design is 52%. The operation time for new design also improving from 82.86s per unit to 40.71s per unit. In this study, the overall operation cost saved is RM16.86 per unit which is RM33.14 reduced to RM 16.28. Hence, this research manages to improve the design efficiency of the product and this will be beneficial to manufacturers and consumers.